All that we are together - Kellen, Alice, 1989- (Kellen, alice, 1989- Let it be novel ;, 2024)
"Three years without seeing him. Three years without Axel. How do you move on from a broken heart? Three years have passed since Axel Nguyen shattered Leah Jones' heart into a million pieces, and Leah has spent every moment of those three years distracting herself from the devastation. She tries to move on with Landon, a guy she meets in college, but she can only truly escape thoughts of Axel when she's painting. At least one good thing has come out of all of it: her dream of exhibiting her work is finally coming true. Axel is achingly aware every day of how much he misses Leah. The moment he learns about Leah's exhibit, Axel can't think about anything else but to go see her. Being in the same room with Leah, as beautiful and magnetic as he remembers, leaves Axel desperate and Leah breathless in his presence. He offers to be her agent; she accepts. One work trip to Paris later leaves Leah and Axel full of pent-up attraction and wondering if their whirlwind romance is a forever kind of love or if it's better off left in the past. International bestselling author Alice Kellen concludes her emotional new adult duology with an evocative and passionate love story for readers of Colleen Hoover, Anna Todd, and books to make you ugly cry"--